Internal communication pattern in TQM manufacturing organizations in Malaysia - Samsudin, Sharina (JGBSE, 2020)
Organizations need to perform; productivity need to be improved and organizations’ activities need to be effective. Therefore, the need for quality improvements are crucial in both manufacturing and service sectors. The main purpose of this paper is to present an analysis of internal communication patterns in TQM implementation in Malaysia manufacturing organizations. This study was done using qualitative in-depth interview method. This is because open ended questions in interviews enable informants to describe their own answers. This qualitative methodological approach refers to the “systematic process analysis”. The study had been carried out in five manufacturing organizations originating from three different continents; two Malaysian local organizations, two eastern and one western organization, and all of them located in Malaysia. In selecting the informants, the study adopts a judgment type of purposive sampling techniques. Results show that the most preferable and reliable medium of communication between superiors and subordinates is still face-to-face meetings although we are in the era of IR4.0. While telephones are popular among the administration staffs. The most preferable forms of communication is the formal internal-operational communication without denying that informal internal-operational communication is also important.